Impacts of robotic process automation on global accounting services - Dahlia Fernandez; Aini Aman (Penerbit Universiti Kebangsaan Malaysia, 2018)
The aim of this study is to understand the impact of Robotic Process Automation (RPA) on Global Accounting Services (GAS) using the institutional logic lens. This study uses an in-depth case study approach in one of the largest global business services firm that provides global accounting services. The result of the study showed that RPA technology has significant impacts on individual and organization resulted in the change and reduction of work, thus reducing the number of employees. Nevertheless, the introduction of new technology in the organization creates unnecessary competition between humans and robots. Although the RPA technology could solve issues involving humans such as disciplinary problems, employee productivity, and human resource shortages, high level of works such as analytical aspect could not be completely replaced by robots and can only be done by humans.